Effect of Dietary Probiotic Lactococcus garvieae JAL37 Supplementation on Growth and Disease Resistance in Tor tambroides Challenged with Aeromonas hydrophila PTF3 - Mahasin, Faiz; Istiqomah, Indah; Handayani, Desy Putri; Isnansetyo, Alim; Murwantoko, Murwantoko; Herath, Tharangani (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. Aeromonas hydrophila PTF3 was identified and analysed as a causative agent of a previously identified hemorrhagic syndrome in Tor tambroides. 2. Lactococcus garvieae JAL37 supplementation in feed can enhance the growth of Tor tambroides fingerlings. 3. Lactococcus garvieae JAL37 can increase the resistance of Tor tambroides fingerlings to Aeromonas hydrophilla PTF3. 4. Relative mRNA levels of ghrelin, GH, and I-FABP genes were increased after 90 days of tor cultivation with Lactococcus garvieae JAL37 supplementation.   Abstract  Mahseer, or tor fish, an indigenous Asian fish of great socio-economic value, is gaining attention as it faces threats to its survival. However, slow growth rates and disease susceptibility remain significant challenges in mahseer cultivation. Feed supplemented with probiotic Lactococcus garvieae JAL37 at a concentration of 1.0 × 10⁸ CFU/g feed, twice weekly, was used in this study to evaluate its effects compared with a control. Triplicate groups of Tor tambroides fingerlings (average weight 1.86 ± 0.09 g) were cultivated for 90 days. Parameters such as growth, intestinal histology, and mRNA expression levels of growth-related genes (ghrelin and I-FABP from the intestine; GH and IGF-1 from the liver) were assessed. Day 90 post-cultivation, mahseer were challenged with an oral infection of Aeromonas hydrophila at 5.0 × 105 CFU/g fish to assess survival rate and mRNA expression levels of pro-inflammatory cytokine-related genes (TNF-α and IL-1β). Weight gain, specific growth rate, and villus length in Tor tambroides fingerlings treated with probiotics showed significant increases (P<0.05). Real-time PCR results indicated upregulated mRNA expression of ghrelin, I-FABP, and GH genes in the probiotic group, whereas IGF-1 gene expression was similar to that in the control group. Probiotic treatment significantly improves the survival rate of T. tambroides after A. hydrophila challenge, while suppressing mRNA expression of TNF-α and IL-1β genes post-challenge. These findings suggest that Lactococcus garvieae JAL37 supplementation can promote growth in Tor tambroides fingerlings and enhance disease resistance against Aeromonas hydrophila.